Ethnomathematics-based Problem Based Learning (PBL) Model to Increase Students’ Critical Thinking in Mathematics Learning - Syahnia, Shovira Maulida; Haenilah, Een Yayah; Perdana, Ryzal; Caswita, Caswita (Lectura : Jurnal Pendidikan, 2024)
Process of learning mathematics in the school that the researcher is aiming for tends to be theoretical, less contextual and pseudo. Applies mathematical concepts in learning with local cultural wisdom able to touch aspects in the daily lives of students. This study aims to apply the ethnomathematics-ground Problem Based Learning (PBL) model to ameliorate critical thinking in mathematics literacy. This explored was type of quasi-experimental explored (pseudo-experiment), with The Non-Equivalent Control Group type design. The population of this study was all fourth grade students at SD Insan Mandiri Bandar Lampung, totaling 121 students. The sample of this studied was determined by intentional slice fashion, which is a sample determination fashion with consideration in opting for the class to be studied and attained by as numerous as 49 students. Data collection technique used valid and dependable test instruments. The data analysis fashion uses a mated t- test with the results attained for the experimental class with a significance value of 0.000 (p<0.05) passing significant changes and in the control class which is not applied to the Ethnomathematics-based PBL model gets a value of 0.070 (p>0.05) indicating that the results of the original test and final test do not witness significant changes. Grounded on the data attained is from the results of this study, the ethnomathematics-ground Problem Based Learning (PBL) model to ameliorate thinking is significant.